How risk informs natural hazard management : a study of the interface between risk modelling for tsunami inundation and local government policies and procedures : a thesis presented for the degree of Doctor of Philosophy in Emergency Management, Massey University, Wellington, New Zealand - Crawford, Miles (Massey University, 2021)
The impact of natural hazards on society and the environment continues to increase, resulting in intolerable and unsustainable financial and social costs. The traditional approach of responding to the hazard once it has occurred is no longer acceptable because it hasn’t always raised awareness of the hazard or allowed communities to pre-emptively take action to protect themselves and their property. It is now more important than ever for governments and communities to proactively understand and prepare for natural hazard risks before hazards occur, so that our vulnerability and exposure to them is reduced when they occur. The costs-benefits of following a proactive approach, rather than a reactive approach are clear, bringing about a change in the way natural hazards are managed, as exemplified by the risk management focus of the Sendai Framework for Disaster Risk Reduction (2015). Despite considerable research and effort in this area, natural hazard risk management struggles to be applied at global, national, and local scales. This illustrates a need to better understand how natural hazard risk is perceived and understood, and how it influences the development of policy frameworks for natural hazard management. In particular, questions remain regarding how risk modelling influences perception of natural hazard risk and application of risk reduction measures at the community level. This research explores how risk informs natural hazard management in Aotearoa New Zealand’s local government. It focusses on how the RiskScape risk modelling tool is used to communicate natural hazard risk for influencing risk awareness and the perceptions of practitioners. It specifically focusses on a tsunami hazard generated in the Hikurangi Subduction Margin as tsunami is Aotearoa New Zealand’s least likely but most significant natural hazard risk. However due to its infrequent occurrence, tsunami is perceived as less risky than other hazards. Focus group sessions and semi-structured qualitative interviews were held with natural hazard risk practitioners within local government, primarily across the Gisborne, Hawke’s Bay, and Wellington regions of Aotearoa New Zealand. The focus groups and interviews explored practitioners’ perceptions on the value of risk modelling tools, particularly ‘RiskScape', for communicating risk and influencing policy development, as well as their thoughts and opinions on natural hazard risk management policy development in general, and with a specific focus on tsunami. These results were then corroborated through document analysis of risk-based tsunami policy and procedure for the regions studied. This research found that while practitioners understand the value of risk modelling for communicating tsunami risk for developing risk awareness and influencing perceptions, RiskScape is not employed widely within local government to achieve risk-based policy and practice. This is partly attributed to trust in risk modelling outputs as well as developmental problems with the RiskScape software. However, the larger part is due to challenges for natural hazard risk management within local government. Local Government’s challenges include lack of guidance, mandate, and collaboration for hazard management; limited risk leadership, understanding and awareness; lack of funding, capacity, and capability; and unavailability of quality data. Underlying each of these challenges are more fundamental challenges relating to the disconnect of the ‘science-policy-practice’ interface, and the interrelated complexity of the challenges which limit the effectiveness of solutions. Along with the limited use of risk modelling, risk-based policy and procedure for tsunami remains scarce. Of the 58 national and local policy documents analysed as part of this research, only three contain specific tsunami risk-based policy. This research proposes the use of ‘systems thinking’ to better understand this complex system of challenges as a whole. This approach can identify intervention points, which can interrupt the system’s dynamics and better apply natural hazard risk management in local government. The science-policy-practice interface is identified as an intervention point; however, tensions for collaboration across this interface limit its effectiveness. A formalised structure, which is mandated by integrative research frameworks, is recommended for how collaboration across the science-policy-practice interface can be improved. An improved science-policy-practice interface would enable the application of further recommendations for overcoming challenges for local government natural hazard risk management. These include developing awareness of natural hazard risk and the cognitive biases that influence risk perceptions; improved understanding of the value in using established risk management approaches; and greater capacity and capability for collecting, managing, and using natural hazard risk data. The outcome would enable bottom-up, co-development of risk modelling, which is trusted and used within local government to better develop risk-based policy and procedure. Through greater use of risk modelling in local government, tsunami risk can be better communicated, and risk-based tsunami policy and procedure can be better achieved. This will reduce tsunami-related losses and enable greater community resilience.
Keywords: Tsunami damage; Risk assessment; New Zealand; Hazard mitigation; Local government; 350703 Disaster and emergency management